Enforcement of intellectual property rights in Africa - Schneider, Marius, 1972-; Ferguson, Vanessa (Oxford University Press, 2020)
Africa is rising: with double-digit growth figures in many countries, its growing middle and upper class, the continent represents an untapped, dynamic, fast-moving and competitive market that businesses can scarcely ignore. Intellectual property right owners are increasingly paying attention to this new African dynamic and have started to invest into African markets. Unfortunately, so have counterfeiters. Taking action against counterfeit and pirated products in Africa is a challenge against which right holders and their representatives often feel overwhelmed. Filling a gap in the market, this is the first book providing a detailed overview of the law and practice in relation to intellectual property rights enforcement in all 54 African countries. For the first time, a comprehensive manual on the conditions and procedures under which the civil and criminal courts, the police and customs take action with regard to counterfeit and pirated goods is available. In order to successfully enforce intellectual property rights in Africa, knowledge of national legislation and procedures, local habits and practices is essential. The book offers a stimulating review of the framework in place for the enforcement of intellectual property rights against pirated and counterfeit goods in all 54 countries and through the two main regional intellectual property organisations, the OAPI and the ARIPO. Arranged in a systematic manner, the reader will find for every jurisdiction information on the factual background, the organisation of the courts, the legal context, the judicial, civil and criminal enforcement of patents, trade marks and copyrights as well as information on the scope, requirements and practical application about customs recordals.